Properties for the thermodynamic control of the complexation of inorganic salt to the modified natural rubber / Assoc. Prof. Dr. Sim Lai Har … [et al.] - Sim, Lai Har; Chan, Chin Han; Kammer, Hans-Werner; Mohd Yusof, Siti Nor Hafiza (Research Management Institute (RMI), 2013)
Solid polymer electrolytes comprise of epoxidized natural rubber (ENR) and methylgrafted natural rubber (MG) as polymer hosts added with LiCI04 were prepared by solution casting technique. Glass transition temperature (Tg) obtained by using differential scanning calorimetry (DSC) and the ionic conductivity evaluated from bulk resistance (Rb) determined using the impedance spectroscopy point towards the higher solubility of the lithium salt in MG rubber. Moreover, two 7gs are observed for the MG-salt electrolyte system whereas only one 7g is obtained for the ENR-salt system at all salt concentrations. The carboxyl group of the MG is found to have a better solvation capability than the oxirane group of ENR. Ionic conductivities {a) and dielectric constants (^) are observed to increase with ascending salt content. However, restricted segmental motion due to the higher degree of Li+ ion coordination to the polar epoxy oxygen of the ENR-50 leads to lower ionic conductivity as compared to ENR-25 and dependency of d on salt concentration is more pronounced at low frequencies from 50 to approximately 1.0 x 104 Hz. A power law dependence of ionic conductivity on salt concentration is also observed in which the lower charge carrier mobility in ENR as compared to MG is in good agreement with its lower conductivity.